2022
DOI: 10.1155/2022/7175108
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Afamin Levels with Nonalcoholic Associated Fatty Liver Disease

Abstract: Afamin is a member of the hepatokine that are strongly associated with various metabolic diseases. The relationship between afamin and nonalcoholic fatty liver disease (NAFLD) remains unclear. This study aimed to explore the correlation between serum afamin levels and NAFLD. We analyzed 88 NAFLD patients and 88 age- and sex-matched healthy controls who took their health examinations at the First Affiliated Hospital, Zhejiang University School of Medicine. The association was further confirmed in 22 biopsy-conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Higher BMI, WC, WHR and fat mass found in GHU subjects could theoretically explain the higher afamin concentrations, however, afamin correlated only with WC among these parameters in AGHD. Interestingly, AST, a common marker of liver injury ( 21 ), was also found higher in GHU subjects, and consistent with previous studies, positively correlated with afamin levels ( 19 , 22 , 23 ). A former study with larger sample size also detected elevated AST levels (39.3 ± 28.4 IU/L) in unsubstituted AGHD patients.…”
Section: Discussionsupporting
confidence: 91%
“…Higher BMI, WC, WHR and fat mass found in GHU subjects could theoretically explain the higher afamin concentrations, however, afamin correlated only with WC among these parameters in AGHD. Interestingly, AST, a common marker of liver injury ( 21 ), was also found higher in GHU subjects, and consistent with previous studies, positively correlated with afamin levels ( 19 , 22 , 23 ). A former study with larger sample size also detected elevated AST levels (39.3 ± 28.4 IU/L) in unsubstituted AGHD patients.…”
Section: Discussionsupporting
confidence: 91%
“…Former studies have reported a strong association of elevated serum afamin with various metabolic disorders, including obesity, MetS, T2DM, NAFLD, and coronary atherosclerosis [ 9 , 28 , 29 ]. In line with these data, in our study, afamin levels were found to be 32.2% higher in the NDO group and nearly two-fold higher in the T2DM group, suggesting that elevated afamin may indicate metabolic disturbance in severe obesity with intact glucose parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the physiological role of AFM is mainly unclear, several studies have discovered a strong correlation between AFM and (obesity, type 2 diabetes mellitus T2DM) [6]. The metabolic syndrome (MetS) and body mass index(BMI) the prevalence of have been reported to be positively correlated with serum afamin levels [7] [8]. Moreover, transgenic mice that overexpress afamin have higher body weights and ( lipoprotein and blood lipid) concentrations [9] [10].…”
Section: Introductionmentioning
confidence: 99%